1990
DOI: 10.1088/0951-7715/3/1/004
|View full text |Cite
|
Sign up to set email alerts
|

A breathing chaos

Abstract: The dynamics of a billiard in a gravitational field between a vertical wall and an inclined plane depends strongly on the angle 0 between wall and plane. Most conspicuously, the relative amount of chaotic versus regular parts of the energy surface shows pronounced oscillations as a function of 0, with distinct minima for 0 near 90"/n (n = 2, 3, . . .). This brearhing is also seen in the Lyapunov exponents. It reflects a repetetive pattern in the linear stability properties of families of periodic orbits. To st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 5 publications
3
32
0
3
Order By: Relevance
“…For elementary applications we refer the reader to [9,17,[20][21][22][23]. The validity of this method for noninvolutory reversing symmetries was given in [7].…”
Section: Theorem 25 (Fixed Set Iteration (Fsi) Method)mentioning
confidence: 99%
See 1 more Smart Citation
“…For elementary applications we refer the reader to [9,17,[20][21][22][23]. The validity of this method for noninvolutory reversing symmetries was given in [7].…”
Section: Theorem 25 (Fixed Set Iteration (Fsi) Method)mentioning
confidence: 99%
“…been highly useful in several applications [9,17,[20][21][22][23]. In [7] it was shown that the method works equally well in case a reversing symmetry is not an involution.…”
Section: U(l)u -1= {L)mentioning
confidence: 99%
“…Для описания хаотических свойств траектории эффективной частицы удобно ис-пользовать результаты, полученные при исследовании движения массивной частицы в угловом биллиарде в постоянном гравитационном поле [13]- [15]. В этих работах од-на из сторон углового биллиарда ориентирована вдоль постоянного гравитационного поля.…”
Section: заряженная композитная частица в постоянном электрическом поunclassified
“…В этих работах од-на из сторон углового биллиарда ориентирована вдоль постоянного гравитационного поля. Так, в работе [13] доказано, что в зависимости от величины угла реализуется хаотическое поведение с положительным показателем Ляпунова. При этом значение показателя Ляпунова и доля площади хаотических режимов на плоскости сечения Пуанкаре осциллируют с изменением величины угла.…”
Section: заряженная композитная частица в постоянном электрическом поunclassified
See 1 more Smart Citation